Economic valuation of El Pinacate y Gran Desierto de Altar Biosphere Reserve - Cáñez-Cota, León Alejandro; Borbón-Morales, Carlos Gabriel; Laborín-Álvarez, Jesús Francisco; Rueda-Puente, Edgar Omar (Ecosistemas y Recursos Agropecuarios, 2025)
Protected natural areas generate multiple benefits, including ecosystem services, many of which remain undervalued due to their intangible nature. Estimating the economic value of these services can support more informed management and policy decisions. This study aims to estimate the recreational value of El Pinacate y Gran Desierto de Altar Biosphere Reserve, located in northwestern Mexico (Sonora State). Using the travel cost method, we surveyed 138 visitors to gather data on their expenditures associated with visiting the reserve. We also applied a zero-truncated negative binomial regression model to account for the nature of the data. The analysis yielded a consumer surplus of 2,475.25 pesos per visitor, and an estimated annual recreational value of 8 964 318.64 pesos for the reserve. These findings underscore the significant social and economic value of protected natural areas and highlight the importance of incorporating such valuations into public environmental policy and budget allocation processes to support long-term conservation efforts.
Keywords: Protected natural area; travel cost method; recreational value